Antidiabetic and Antihyperlipidemic Effects of Clitocybe nuda on Glucose Transporter 4 and AMP-Activated Protein Kinase Phosphorylation in High-Fat-Fed Mice. (16th January 2014) - Chen, Mei-Hsing; Lin, Cheng-Hsiu; Shih, Chun-Ching
Abstract : The objective of this study was to evaluate the antihyperlipidemic and antihyperglycemic effects and mechanism of the extract of Clitocybe nuda (CNE), in high-fat- (HF-) fed mice. C57BL/6J was randomly divided into two groups: the control (CON) group was fed with a low-fat diet, whereas the experimental group was fed with a HF diet for 8 weeks. Then, the HF group was subdivided into five groups and was given orally CNE (including C1: 0.2, C2: 0.5, and C3: 1.0 g/kg/day extracts) or rosiglitazone (Rosi) or vehicle for 4 weeks. CNE effectively prevented HF-diet-induced increases in the levels of blood glucose, triglyceride, insulin (P < 0.001, P < 0.01, P < 0.05, resp.) and attenuated insulin resistance. By treatment with CNE, body weight gain, weights of white adipose tissue (WAT) and hepatic triacylglycerol content were reduced; moreover, adipocytes in the visceral depots showed a reduction in size. By treatment with CNE, the protein contents of glucose transporter 4 (GLUT4) were significantly increased in C3-treated group in the skeletal muscle. Furthermore, CNE reduces the hepatic expression of glucose-6-phosphatase (G6Pase) and glucose production. CNE significantly increases protein contents of phospho-AMP-activated protein kinase (AMPK) in the skeletal muscle and adipose and liver tissues. Therefore, it is possible that the activation of AMPK by CNE leads to diminished gluconeogenesis in the liver and enhanced glucose uptake in skeletal muscle. It is shown that CNE exhibits hypolipidemic effect in HF-fed mice by increasing ATGL expression, which is known to help triglyceride to hydrolyze. Moreover, antidiabetic properties of CNE occurred as a result of decreased hepatic glucose production via G6Pase downregulation and improved insulin sensitization. Thus, amelioration of diabetic and dyslipidemic states by CNE in HF-fed mice occurred by regulation of GLUT4, G6Pase, ATGL, and AMPK phosphorylation.